Neuroscience, consciousness and spirituality - Walach, Harald; Schmidt, Stefan; Jonas, Wayne B.; SpringerLink (Online service). (New York Springer, 2011)
"Neuroscience, Consciousness and Spirituality presents a variety of perspectives by leading thinkers on contemporary research into the brain, the mind and the spirit. This volumes aims at combining knowledge from neuroscience with approaches from the experiential perspective of the first person singular in order to arrive at an integrated understanding of consciousness. Individual chapters discuss new areas of research, such as near death studies and neuroscience research into spiritual experiences, and report on significant new theoretical advances. From Harald Walach?s introductory essay, "Neuroscience, Consciousness, Spirituality--Questions, Problems and Potential Solutions," to the concluding chapter by Robert K. C. Foreman entitled "An Emerging New Model for Consciousness: The Consciousness Field Model," this book represents a milestone in the progress towards an integrated understanding of spirituality, neuroscience and consciousness. It is the first in a series of books that are dedicated to this topic."--Publisher?s website.
Neuroscience, consciousness, spirituality -- Questions, problems and potential solutions: an introductory essay / H. Walach -- Mindfulness in east and west-is it the same? / S. Schmidt -- Setting our own terms: how we used ritual to become human / M.J. Rossano -- Neuroscience and spirituality -- Findings and Consequences / M. Beauregard -- Consciousness: a riddle and a key in neuroscience and spirituality / D. Jeanmonod -- Generalized entanglement- a nonreductive option for a phenomenologically dualist and ontologically Monist view / H. Walach, H. Römer -- Complementarity of phenomenal and physiological observables: a primer on generalised quantum theory and its scope for neuroscience and consciousness studies / H. Römer, H. Walach -- Hard problems in philosophy of mind and physics: do they point to spirituality as a solution? / N. von Stillfried -- Brain structure and mditation -- How spiritual practice shapes the brain / U. Ott, B.K. Hölzel & D. Vaitl -- Neurophysiological correlates to psychological trait variables in experienced meditative practitioners / T. Hinterberger, et. al. Reconsidering the metaphysics of science from the inside out / J.W. Schooler, J.N. Schooler -- Mindfulness meditation: deconditioning & changing view / H. Barendregt -- Endless Consciousness -- A concept based on scientific studies on near-death experience / P. van Lommel -- The hard problem revisited: from cognitive neuroscience to Kabbalah and back again / B.L. Lancaster -- Towards a neuroscience of spirituality / W.B. Jonas -- Sufism and rapid wound healing / H. Hall -- An emerging new model for consciousness: the consciousness field model / R.K.C. Forman.
Electronic reproduction.
Keywords: Consciousness; Neurosciences; Spirituality; Electronic books